Gérer l’alternance, ordonner un monde en mouvement - Laura Merla; Bérengère Nobels (Recherches Sociologiques et Anthropologiques, 2021)
Through the analysis of the discourses of 21 Belgian adolescents aged 10 to 16 on their lived experiences of a multilocal lifestyle, this article sheds light on how the materiality that surrounds these young people allows them to order their world into a lived space and establish links and continuities in the experience of mobility. Drawing on material studies and their application to the field of family studies, we begin by identifying the main functions that everyday objects perform in the lives of young people living in separated families. After presenting our method, we present two ensembles of material practices deployed by children in egalitarian housing and which consist, on the one hand, (1) in ordering, distinguishing and anchoring themselves in each living space by fixing “parked objects”, and on the other hand, (2) in creating permanence and continuity in movement with “objects in transit”. We also assume that these practices and the meaning lent to them are constructed at the intersection between their own aspirations and the framework set for them by their family environment (marked by material and spatial constraints, educational values and styles, and specific temporalities).